Identification of a recessive gene RgM4G52 conferring red glume, stem, and rachis in a Triticum boeoticum mutant - Chen, Longyu; Zhang, Junqing; Ma, Pan; Miao, Yongping; Wu, Lei; Zhou, Ke; Yang, Jiaru; Zhang, Minghu; Liu, Xin; Jiang, Bo; Hao, Ming; Huang, Lin; et al. (Frontiers in Plant Science, 2024)
Anthocyanins are plant secondary metabolites belonging to the polyphenol class of natural water-soluble phytopigments. The accumulation of anthocyanins in different plant tissues can improve plant survival under adverse conditions. In addition, plants with the resulting colorful morphology can be utilized as landscape plants. Triticum boeoticum (syn. Triticum monococcum ssp. aegilopoides, 2n=2x=14, A b A b ) serves as a valuable genetic resource for the improvement of its close relative common wheat in terms of enhancing resilience to various biotic and abiotic stresses. In our previous study, the EMS-mutagenized mutant Z2921 with a red glume, stem, and rachis was generated from T. boeoticum G52, which has a green glume, stem, and rachis. In this study, the F1, F2, and F2:3 generations of a cross between mutant-type Z2921 and wild-type G52 were developed. A single recessive gene, tentatively designated RgM4G52, was identified in Z2921 via genetic analysis. Using bulked segregant exome capture sequencing (BSE-Seq) analysis, RgM4G52 was mapped to chromosome 6AL and was flanked by the markers KASP-58 and KASP-26 within a 3.40 cM genetic interval corresponding to 1.71 Mb and 1.61 Mb physical regions in the Chinese Spring (IWGSC RefSeq v1.1) and Triticum boeoticum (TA299) reference genomes, respectively, in which seven and four genes related to anthocyanin synthesis development were annotated. Unlike previously reported color morphology-related genes, RgM4G52 is a recessive gene that can simultaneously control the color of glumes, stems, and rachis in wild einkorn. In addition, a synthetic Triticum dicoccum-T. boeoticum amphiploid Syn-ABA b -34, derived from the colchicine treatment of F1 hybrids between tetraploid wheat PI 352367 (T. dicoccum, AABB) and Z2921, expressed the red stems of Z2921. The flanking markers of RgM4G52 developed in this study could be useful for developing additional common wheat lines with red stems, laying the foundation for marker-assisted breeding and the fine mapping of RgM4G52.